Occupational therapists as case managers within the medico-legal field: perceptions of occupational therapists working as case managers - Perridge, Emma (My University, 2020)
The global private healthcare industry has shifted towards case management in order to ensure a smoother healthcare process is maintained from beginning to end. Case management is a role of occupational therapists that is performed in various contexts in South Africa e.g. the insurance sector, health consulting to manage long term incapacity and disability in the workplace, the Road Accident Fund to aid motor vehicle accident victims and within the vocational rehabilitation service (Govender, et al., 2018). However, literature does not mention occupational therapists’ involvement within the medico-legal field (unless employed or providing services directly to the Road Accident Fund) e.g. case managers performing consulting work for trusts or curators. The medico-legal context is a broad description used by occupational therapists to describe a field of practise where occupational therapists work with the legal fraternity to help them quantify or qualify a legal case. Occupational therapists are referred injured patients from the state or private attorneys and asked to evaluate their functional abilities and to write recommendations in medio-legal reports and testify as expert witness (van Biljon, 2013). van Biljon (2013) notes that occupational therapists do not know if their recommendations in the medico-legal reports are ever implements and therefore highlights the need for case managers. These case managers may perform tasks specific to the context and not defined in traditional case management literature. This could include providing advice to the trust (e.g. on housing, vehicle purchasing and required care) or writing motivational reports to the Master of the High Court. This is a service being offered and, therefore, there is a need to explore the medico-legal context and the gap that exists in literature of describing the role of occupational therapists as case managers within the medico-legal context. The intention of this study was to explore the perceptions of selected South African occupational therapists about their work and responsibilities as case manager in a medico-legal context. Three objectives guided the study, exploring the perceptions of iv OCCUPATIONAL THERAPISTS AS CASE MANAGERS WITHIN THE MEDICO-LEGAL FIELD: PERCEPTIONS OF OCCUPATIONAL THERAPISTS WORKING AS CASE MANAGERS their roles and responsibilities, their skills and knowledge, and of their preparedness to perform their case management role. A qualitative research approach and a cross sectional descriptive design were used to complete this study. Data were gathered through seven semi-structured interviews with open-ended questions, which yielded the qualitative data. Results offered three themes (each answering one of the three objectives), namely a holistic role approach, integrated body of knowledge and skills as well as broad experience Occupational therapy participants perceive themselves as making use of a holistic approach to fulfil their roles and responsibilities as clinical case managers working in the medico-legal context. They perceive themselves to have an integrated body of knowledge and skills, which support their ability to perform their role. Some thought they were prepared for their role, while others perceived themselves to be unprepared. The results of this study provide guidance as to the role and responsibilities of a case manager and will assist occupational therapists currently working as case managers to increase their understanding and knowledge of their role. It will therefore enhanced practice by making more appropriate recommendations for clients during and after medico-legal trials. The results will provide a reference to occupational therapists working in this field to better coordinate the care of clients, which would ultimately benefit the latter. It may also encourage more occupational therapists to undertake such roles, as they have a better understanding of what the role entails, what would be expected of them and to prepare accordingly.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine in Occupational Therapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2020